2012
DOI: 10.1364/ao.51.006125
|View full text |Cite
|
Sign up to set email alerts
|

Generation of optical vortices in spun multihelicoidal optical fibers

Abstract: We have theoretically studied long-period spun l-helicoidal fibers and their ability to generate singular beams from regular ones. On the basis of perturbation theory in the presence of degeneracy, applied to the scalar waveguide equation, we obtained the structure of coupled modes of such fibers and their spectra. It is shown that the coupled modes consist of the fields, which taken separately bear topological charges that differ by l units. We have numerically studied the process of the passage of a Gaussian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 21 publications
2
12
0
Order By: Relevance
“…As seen from Table 3, OAM beams with the charge 1 and 3 can be generated in L-1-CFGs, while those with not only charge N revealed in [6], but also charge N 2 can be generated in L-N-CFGs (N ≥ 2). Specifically, OAM beams with the charge 2 and 4 can be generated in L-2-CFGs, which will be used for converter design later.…”
Section: Hementioning
confidence: 97%
See 4 more Smart Citations
“…As seen from Table 3, OAM beams with the charge 1 and 3 can be generated in L-1-CFGs, while those with not only charge N revealed in [6], but also charge N 2 can be generated in L-N-CFGs (N ≥ 2). Specifically, OAM beams with the charge 2 and 4 can be generated in L-2-CFGs, which will be used for converter design later.…”
Section: Hementioning
confidence: 97%
“…It was demonstrated that long-period l-helicoidal fibers can generate an OAM beam with charge l [6]. The aim in this Letter is to demonstrate all the charged OAM beams possibly generated in chiral fiber gratings (CFGs) with multiple-fold rotation symmetry in the cross section.…”
mentioning
confidence: 98%
See 3 more Smart Citations